Development of Micro Hydro Generator using Rainwater for Domestic Usage - Pusparini Dewi Abd Aziz; Sarina Zakaria; Nor Shafiqin Shariffuddin; Mohamad Miqdad Abd Aziz (Journal of Engineering Technology, 2016)
The main sources of energy used for the generation of electrical energy are water, fuels, nuclear energy and other related source that have been widely used all over the world. For water energy, hydro generator is used to convert kinetic energy from the water flow into electricity. In hydroelectric power plants, each generator is capable in generating from few kW to thousands of MW. However for domestic usage, a micro hydro generator can be used if the generating capacity is less than 100kW. Micro hydro can provide alternative renewable energy sources especially in areas like small rivers, stream flowing or building. The choice of energy source depends on several factors, including availability, economic and energy and power requirements. Micro hydro power is cost-effective than any other form of renewable power. Micro hydro used in this project has output less than 500W. This project involves two parts of the generator; mechanical and electrical. The mechanical part involves the process of rainwater intake. This is the part where the beginning of the power generation of the system. It involves the design of the casing, turbine and a set of rotor and stator. Meanwhile, the electrical part is more on the power conversion that employed components such as rectifier, DC load, DC-DC converter, charging circuit and battery for storage purposes. In the end of the project, the micro hydro generator functions as expected and able to produce output power more than 2.5 Watt with 8V DC voltage and 250mA DC current at the highest speed of rotation